The Effect of Soursop and Betel Leaf Extracts as Organic Pesticides in Pest Control of Spodoptera exigua (Lepidoptera: Noctuidiae) on Onion (Alium ascalonicum L.) Cultivation - Syahputra, Bagas Sriadi; Ginting, Tri Yaninta (Universitas Labuhanbatu, 2024)
Spodoptera exigua is a major pest in onion cultivation. S.exigua larvae have a rapid spread and can cause yield losses of up to 20-100% if not controlled. Soursop leaf extract and betel leaf pesticides can cause mortality in S.exigua pests. This is due to secondary metabolites found in soursop leaf extract and betel leaf such as acetogenin, alkaloids, flavonoids, terpenoids, steroids, saponins and tannins. The purpose of this study was to determine the effectiveness of soursop leaf extract and betel leaf and the combination of both in controlling S.exigua pests. This study used a non-factorial Complete Randomized Design method with 7 treatments, namely P0 = Control, P1 = 30% soursop leaf extract, P2 = 60% soursop leaf extract, P3 = 30% betel leaf extract, P4 = 60% betel leaf extract, P5 = 15% soursop leaf extract + 15% betel leaf extract, P6 = 30% soursop leaf extract + 30% betel leaf extract. The results showed that the P2 treatment had the highest mortality rate with 67.50% mortality and the P3 treatment had the lowest mortality rate of 25.00%. Symptoms of attack show that the larvae are initially actively eating and then begin to stay away from feed, the larvae then show a change in color to brown and slowly remain still and die. The duration of pest mortality showed the fastest mortality occurred in 24 hours with the death of 20 larvae, larval mortality continued to increase with each observation. Testing on natural enemies showed results that the use of soursop leaf extract did not show any death